Application of invariant moment method for HAPS ISAR imaging with micro parts - Zhao-qun QI; Xiao-jun JING; Si-qing YOU; Hai-bin SUN (Tongxin xuebao)
To resolve the micromotion in the HAPS(high altitude platform station) ISAR system,the invariant moment method for ISAR imaging with micro parts was proposed.Firstly,invariant moment tool was applied to classify the echoes of different sub-aperture,and then the sub-aperture echoes reducing the quality of image was separated.Finally the remaining echoes were used to do sub-aperture splicing imaging.From the simulation results,the algorithm is proved to be simple and can improve the quality of ISAR image obviously.